(untitled) (Scientific journal of the Fergana State University, 2023)
This article discusses the role of the main gymnastics and games in the State Education Standard. In addition, it is reported that the use of basic gymnastics in kindergartens and the physical training of pre-school age children are mainly gymnastic exercises.